ANALYSIS OF THE EFFECTIVENESS OF FERTILIZER SUBSIDY POLICY FOR RICE FARMERS IN SUKAMANAH VILLAGE, JATINUNGGAL DISTRICT - Nurjanah, Teti; Marliani, Yayu Ulfah; Kusumawati, Eni (Universitas Jambi, 2025)
ABSTRACTThis research aims to analyze the effectiveness of fertilizer subsidy policies for rice farmers in Sukamanah Village, Jatiunggal District. The research method uses a quantitative descriptive approach. The number of samples used in this research was 39 respondents. The sampling technique uses cluster sampling with the two stage cluster sampling method. The data analysis used is 4 indicators for measuring effectiveness including Right Price, Right Quantity, Right Time, Right Place. The results of this research indicate that the fertilizer subsidy policy for rice farmers in Sukamanah Village is still not effective. Based on four indicators. This is because the price indicators, quantity indicators and time indicators have not been met. Meanwhile, the exact indicators for the location have been met.